Effect of single and repeated oral doses of telithromycin on cardiac QT interval in healthy subjects - Démolis, Jean-Louis; Vacheron, Françoise; Cardus, Stéphane; Funck-Brentano, Christian (Clinical pharmacology and therapeutics, 2003)
Telithromycin is the first member of a new class of antimicrobials-the ketolides. The main objective of this study was to assess the effect of various oral doses of telithromycin on QT interval during single and repeated administrations. Seventeen men and 17 women participated in double-blind, placebo-controlled, crossover studies. Of these subjects, 18 (9 men and 9 women) received single and repeated oral doses of telithromycin (800 mg daily), clarithromycin (500 mg twice daily), or placebo (protocol 1). The other 16 subjects received a single oral dose (800 mg, 1600 mg, and 2400 mg) of telithromycin or placebo (protocol 2). At the time of expected telithromycin maximum concentration, several electrocardiographic recordings were obtained at rest and during the course of a submaximal exercise test. QT intervals were measured within a wide range of R-R intervals in each subject. ANOVA showed that telithromycin did not increase QT interval at any dose compared with placebo. The greatest effect observed during any study period was a mean (+/-SD) change in QT-interval duration of 4.2 +/- 15.2 ms (ie, +1.2% +/- 4.0%, P not significant) at R-R = 1000 ms after repeated doses of 800 mg telithromycin. Outlier values (change in Bazett QTc from baseline >60 ms) from resting 12-lead electrocardiograms did not differ across treatment groups, including placebo. Telithromycin administered as repeated doses of 800 mg (recommended doses) or as single doses of up to 3 times this recommended dose did not increase the QT interval at any heart rate at rest and during effort. Telithromycin did not prolong QT-interval duration when administered to healthy young male and female subjects.